The mediating role of absorptive capacity in the relationship between transformational leadership and corporate entrepreneurship - Samer Ali Al-Shami; Salama Jamal Rafeea; Massila Kamalrudin; Tika Widiastuti; Abdullah Al Mamun (Cogent Business & Management, 2023)
Absorptive capacity is widely acknowledged as a critical driver of innovation, business development, and self-renewal through the acquisition, transformation, assimilation, and application of knowledge. Despite the importance of the relationship between transformational leadership and corporate entrepreneurship, there exists a research gap due to the insufficient exploration of the mediating impact of absorptive capacity. This study endeavors to fill the existing research gap by delving into the interplay between transformational leadership and corporate entrepreneurship, taking absorptive capacity into consideration as a mediating factor. Surveys were collected from 154 middle managers representing a broad range of healthcare institutions in the United Arab Emirates. The study utilized a two-step structural equation modelling approach and provided empirical evidence to support the hypothesis that absorptive capacity mediates the relationship between transformational leadership and corporate entrepreneurship. These findings contribute to the resource-based view theory by demonstrating the effective role of transformational leadership in promoting corporate entrepreneurship through the development of absorptive capacity.
Keywords: 650; absorptive capacity; corporate; entrepreneurship; healthcare; leadership; transformational